Shaping the day a history of timekeeping in England and Wales 1300-1800 - Glennie, Paul; Thrift, Nigel (Oxford University Press, 2009)
Timekeeping is an essential activity in the modern world and we take it for granted that our lives our shaped by the hours of the day. Yet what seems so ordinary today is actually the extraordinary outcome of centuries of technical innovation and circulation of ideas about time.